INTEGRATING HEALTH EDUCATION AND FAMILY SUPPORT TO ENHANCE HEALTHY LIFESTYLE IN ELDERLY POPULATIONS - Putra, Kusuma Wijaya Ridi; Ana, Karisma Dwi (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2025)
This community-based program aimed to promote healthy lifestyles among elderly populations through an integrated approach combining health education and family support. The intervention was implemented at the Mojoagung Primary Health Center, Jombang Regency, East Java, Indonesia, during October 2025. A total of 40 elderly participants and 40 family members joined a two-week program consisting of group education sessions, family support meetings, and home visits facilitated by health cadres and nursing students. Evaluation included pre- and post-assessments of knowledge, attitudes, and healthy behavior practices. Results showed a 22 % increase in knowledge scores, a 28 % rise in self-reported healthy behaviors, and a 72 % improvement in caregivers’ competence, exceeding targeted outcomes. Attendance rates among elderly participants and caregivers reached 85 % and 74 %, respectively, with 92 % program fidelity. Participants reported high satisfaction and perceived relevance of the program. These findings suggest that integrating health education with structured family support effectively enhances health literacy, behavioral adherence, and caregiving competence among older adults. The approach demonstrates feasibility and acceptability within Indonesia’s community-based primary healthcare system, emphasizing the importance of family engagement in promoting healthy ageing. Further studies with larger samples and extended follow-up periods are recommended to assess long-term sustainability and clinical impacts of this model.